Timor-Leste Gender and Investment Climate Reform Assessment - Hedditch, Sonali; Manuel, Clare (International Finance Corporation, Washington, DC, 2017)
This report is one of six gender and investment climate reform assessments undertaken in six Pacific nations including Timor-Leste. The report analyses gender-based investment climate barriers which constrain private sector development and identifies solutions to address them. Four key investment climate areas are considered: public private dialogue; starting and licensing a business; access to justice and alternative dispute resolution; and access to, and enforcement of, rights over registered land. In each area the report considers legal, regulatory, and administrative barriers to private sector development with a gender perspective. It makes recommendations aimed at ensuring that women benefit from ongoing efforts to improve Timor-Leste’s investment climate on the same basis as their male counterparts. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.